Early hydration study of a new cementitious mineral – Calcium aluminophosphate. (30th September 2020) - Ding, Zhu; Liu, Pai; Zhou, Zhi-Wei; Zhang, Ning; Liu, Biao
Highlights: A new cementitious mineral - calciumcalcium aluminophosphate was firstly studied. CAP has a very high strength development rate from 1 day to 7 day. The hydrates of the mineral are C–A–P–H and C–A–H gels, and a small amount of crystal products. The early hydration of calciumcalcium aluminophosphate mineral is divided into five stages. Abstract: Aluminophosphate cement (APC) is a newly designed cementitious material, its clinker mineral composition is different from the existing Portland cement, aluminate cement, and sulphoaluminate cement. The main mineral compounds of APC clinker are calcium aluminophosphate (CAP), monocalcium aluminate (CA), and tricalcium phosphate (C3 P). CAP is a newly invented ternary compound, and the other two are known minerals. In this study, CAP was prepared by a sol–gel method and high-temperature calcination. The early hydration process and microstructure of the CAP hydration paste were analyzed by measuring the hydration heat and using X-ray diffraction, scanning electron microscopy, and X-ray computed tomography methods. The results showed that the main hydration products in the hydrated CAP paste were C–A–P–H and C–A–H gels. Small quantities of crystal products, hydrated calcium phosphate (3CaO·6P2 O5 ·10H2 O), and hydrated calcium aluminate (C2 AH8 ) were also present. The early hydration process of the CAP was divided into five stages: initial hydration, induction, acceleration, deceleration, and stabilization. The CAP paste microstructure was observed by XCT with 3D reconstruction. The results of this study will be helpful for understanding the hydration mechanism and microstructure of the new cement mineral.